Production and Ultrastructure of Lysozyme and Ethylenediaminetetraacetate-Lysozyme Spheroplasts of Escherichia coli - Birdsell, D. C. (1967)
Spheroplast production by lysozyme and ethylenediaminetetraacetate (EDTA) was examined as a means of obtaining osmotically sensitive cells for studies of enzyme localization. Physiologically young cells plasmolyzed with 0.5 m sucrose in 0.01 m tris(hydroxymethyl)aminomethane (Tris) buffer (pH 7, 8, or 9) were quantitatively converted to plasmolyzed osmotically sensitive rods after lysozyme treatment. Although such cells were osmotically sensitive, a 1:1 dilution in Tris buffer was necessary for conversion of rods into spheroplasts. Addition of EDTA resulted in a rapid conversion of the plasmolyzed spheroplasts into spherical structures devoid of a plasmolysis vacuole. These structures, which we call EDTA-lysozyme spheroplasts, contained a number of attached membranes. We believe that this conversion results from a weakening of the outer trilaminar component of the cell wall by EDTA, resulting in the collapse of the plasmolysis vacuole. Dilution of sucrose below 0.15 m also resulted in the collapse of the plasmolysis vacuole. Both the lysozyme spheroplasts and the EDTA-lysozyme spheroplasts were osmotically sensitive. Thin sections of the EDTA-lysozyme spheroplasts demonstrated that the outer trilaminar component of the cell wall was broken, exposing large areas of the cytoplasmic membrane to the environment.